Polycentricity, Agglomeration, and Industrial Air Pollution in the Chinese City-Regions - Han, Xu; Dou, Jianmin; Tang, Chenghui (Frontiers in Environmental Science, 2022)
Abstract This paper creatively studies the relationship between urban spatial structure and air pollution based on agglomeration theory from the perspective of polycentricity and monocentricity. We extend Ciccone and Hall (1996) production density model by considering air pollution originating from industrial production as non-expected output and introducing the spatial organization form in order to examine whether polycentricity has more obvious emission reduction effect under the same agglomeration degree, and explain it from three mechanisms: environmental regulation integration, energy utilization efficiency and environmental treatment capacity. An econometric analysis across 21 city-regions in China from 2003 to 2016 shows that spatial structure matters: polycentricity is associated with lower industrial pollution emission intensity, but the emission reduction effect of polycentricity depends on regional agglomeration. The higher the regional agglomeration, the greater the emission reduction effect. The heterogeneity test also indicates that the geographical compactness and unified administration of city-regions strengthen this emission reduction effect. In addition, the mediating effect test verifies the three mechanisms proposed in this paper, among which energy utilization efficiency effect plays a major role. These findings provide a new perspective for the study of China’s industrial air pollution from spatial policy.